Illegal Cigarettes from a Legal Perspective: The Discrepancybetween Excise Regulations and Law Enforcement in the Field - Imora Helguera; Aries Isnandar; Azis Akbar Ramadhan (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
The widespread circulation of illegal cigarettes in Indonesia causes significant economic, legal, and social losses, highlighting a persistent gap between strict excise regulations and weak field enforcement. This study aims to analyze the legal framework governing tobacco excise and examine the key factors that undermine law enforcement against illegal cigarettes. Using a normative legal method, the research analyzes secondary data from legal documents and the literature. The findings reveal that the regulation-enforcement gap is driven by limited supervisory capacity, the complexity of illegal distribution networks, persistently high market demand fueled by price disparities, poor interagency coordination, and inconsistent enforcement of sanctions. Consequently, the study concludes that strengthening law enforcement capacity, enhancing coordination among Customs, police, and local governments, using information technology for surveillance, and increasing public participation are essential strategies. The research recommends that future policies adopt a multidisciplinary approach that integrates legal, economic, and social dimensions and that further empirical studies be conducted to measure enforcement effectiveness more comprehensively, thereby ensuring more sustainable excise law enforcement in Indonesia. Peredaran rokok ilegal di Indonesia menimbulkan kerugian ekonomi, hukum, dan sosial yang signifikan, sekaligus menunjukkan kesenjangan persisten antara regulasi cukai yang ketat dan lemahnya penegakan hukum di lapangan. Penelitian ini bertujuan menganalisis kerangka hukum cukai tembakau dan mengkaji faktor utama penyebab ketidakefektifan penegakan hukum terhadap rokok ilegal. Dengan metode hukum normatif melalui pendekatan perundang-undangan dan konseptual, penelitian ini menganalisis data sekunder dari dokumen hukum dan studi pustaka. Temuan menunjukkan bahwa kesenjangan regulasi dan penegakan hukum disebabkan oleh kapasitas pengawasan yang terbatas, kompleksitas jaringan distribusi ilegal, tingginya permintaan pasar akibat perbedaan harga, koordinasi antarlembaga yang lemah, serta penerapan sanksi yang tidak konsisten. Penelitian ini menyimpulkan bahwa penguatan kapasitas aparat penegak hukum, peningkatan koordinasi antara Bea Cukai, kepolisian, dan pemerintah daerah, pemanfaatan teknologi informasi untuk pengawasan, serta peningkatan partisipasi publik merupakan strategi esensial. Rekomendasi penelitian adalah bahwa kebijakan masa depan harus mengadopsi pendekatan multidisiplin yang mengintegrasikan aspek hukum, ekonomi, dan sosial, serta perlunya studi empiris lebih lanjut untuk mengukur efektivitas penegakan hukum secara komprehensif demi terwujudnya penegakan hukum cukai yang berkelanjutan di Indonesia.